2021
DOI: 10.1039/d1nj01088c
|View full text |Cite
|
Sign up to set email alerts
|

α-MoC1−x nanorods as an efficient hydrogen evolution reaction electrocatalyst

Abstract: As one type of efficient non-precious metal catalysts for the hydrogen evolution reaction (HER), molybdenum carbides have attracted much attention in recent decades. Efforts have been devoted to the structure...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…The charge redistribution causes ion accumulation from aqueous solution and consequently an elevated C dl value. MoC/Mo 2 C (II) therefore has the highest ECSA with the largest number of active sites exposed on the surface, consistent with its outstanding HER performance. Figure d displays the fitted Nyquist impedance curves at an overpotential of 200 mV, and the inserted model is the equivalent circuit . Mo 2 C shows the largest semicircle in the high-frequency zone, indicating the largest charge-transfer resistance (18 Ω).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The charge redistribution causes ion accumulation from aqueous solution and consequently an elevated C dl value. MoC/Mo 2 C (II) therefore has the highest ECSA with the largest number of active sites exposed on the surface, consistent with its outstanding HER performance. Figure d displays the fitted Nyquist impedance curves at an overpotential of 200 mV, and the inserted model is the equivalent circuit . Mo 2 C shows the largest semicircle in the high-frequency zone, indicating the largest charge-transfer resistance (18 Ω).…”
Section: Resultsmentioning
confidence: 99%
“…Figure 4d displays the fitted Nyquist impedance curves at an overpotential of 200 mV, and the inserted model is the equivalent circuit. 40 Mo 2 C shows the largest semicircle in the high-frequency zone, indicating the largest charge-transfer resistance (18 Ω). For all of the other samples, MoC/Mo 2 C (II) shows the smallest resistance (3.6 Ω), in contrast to MoC/Mo 2 C (I) (6.3 Ω), MoC/Mo 2 C (III) (6.3 Ω), and then MoC (10.7 Ω), demonstrating the best charge-transfer ability.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In the recent years, the studies of transition-metal oxides, , carbides, , nitrides, , sulfides, phosphides, and so forth have gained considerable attention. Specifically, phosphides have been widely discussed owing to their high HER catalytic activity and low cost.…”
Section: Introductionmentioning
confidence: 99%
“…Molybdenum carbide (Mo 2 C) films have attracted extensive attention owing to its advantages of high melting point, high hardness, excellent thermal stability, and mechanical properties [1]. Mo 2 C films have been widely used in various fields, such as catalysis [2][3][4], superconductivity [5,6], and Bragg mirrors [7][8][9]. The applications of Mo 2 C films are largely dependent on the phase transitions, especially for use as catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Wan et al prepared multiple phases of molybdenum carbide (α-MoC 1-x , β-Mo 2 C, η-MoC, and γ-MoC) as electrocatalysts for the hydrogen evolution reaction (HER); they found that γ-MoC has great potential as catalyst for HER [3]. Yin et al synthesized porous α-MoC 1-x nanorods via controlled carburization of MoO 3 nanorod precursors, which exhibited significantly enhanced HER performance under both acidic and alkaline conditions [4]. Liu et al induced the transition from α to β phase in 2D α-Mo 2 C crystals using electron beam irradiation, they found that α/β Mo 2 C with sharp interfaces could improve superconductivity [5].…”
Section: Introductionmentioning
confidence: 99%